2019
DOI: 10.1080/21691401.2019.1577877
|View full text |Cite
|
Sign up to set email alerts
|

Inonotus obliquus polysaccharide ameliorates dextran sulphate sodium induced colitis involving modulation of Th1/Th2 and Th17/Treg balance

Abstract: Inflammatory bowel disease (IBD) is an intestinal chronic inflammatory disease, and is related to imbalance of CD4 þ T subsets. However, the current treatments of chronic colitis are not ideal and have potential side effects. Therefore, more effective and safer biologically active substances which are extracted from natural plants have been widely concerned. In this study, it was found that Inonotus obliquus polysaccharides (IOP), the main bioactive constituent of Inonotus obliquus, can alleviate dextran sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Recently, many reports studying polysaccharides of natural origin have indicated that there are a variety of biological functions, such as anti-tumor, immune stimulation, antibacterial, anti-oxidant, with various polysaccharides (Song et al, 2008;Chen et al, 2010Chen et al, , 2019Opoku-Temeng et al, 2019;. The antitumor effect of these polysaccharides is mainly exerted by regulating the host's immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many reports studying polysaccharides of natural origin have indicated that there are a variety of biological functions, such as anti-tumor, immune stimulation, antibacterial, anti-oxidant, with various polysaccharides (Song et al, 2008;Chen et al, 2010Chen et al, , 2019Opoku-Temeng et al, 2019;. The antitumor effect of these polysaccharides is mainly exerted by regulating the host's immune function.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that IOP can inhibit the induction of NO and other similar cytokines, a phenomenon that has been associated with COVID-19 [62]. Similarly, in another experiment on inflammatory bowel disease, Inonotus obliquus polysaccharides (IOP) were shown to alleviate inflammatory responses by inhibiting JAK-STAT signalling pathways that regulate the release of T Helper subsets [63]. Furthermore, the extract of chaga mushroom was also found to possess anticancer properties; however, the exact mechanism of action of these polysaccharides is still unknown [64,65].…”
Section: Inonotus Obliquus Antiviral Anti-inflammatory Effectsmentioning
confidence: 96%
“…It is well established that the imbalance of Th1/Th2 and Th17/Treg cells is strongly associated with the pathogenesis of CP/CPPS [ 13 , 35 ]. The imbalance of Th1/Th2 is involved in the allergic disease and graft-versus-host disease and is related to autoimmune disorders [ 36 ]. It also has a role in the development of CP/CPPS.…”
Section: Discussionmentioning
confidence: 99%